2021
DOI: 10.14260/jemds/2021/240
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intravenous Lignocaine and Dexmedetomidine for Attenuation of Hemodynamic Stress Response to Laryngoscopy and Endotracheal Intubation

Abstract: BACKGROUND The purpose of the present study was to evaluate the efficacy of intravenous lignocaine 1.5 mg / kg & intravenous dexmedetomidine 1 mcg / kg for attenuating the haemodynamic response to laryngoscopy & endotracheal intubation in patients undergoing elective surgery under general anaesthesia. METHODS In this prospective randomised, comparative, clinical study, 60 patients were randomly divided into 2 groups, among them 30 patients were given infusion of 1.5 mg / kg IV lignocaine, diluted to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…Seangrung et al [14] found that difference in mean values of SBP, DBP and MAP were significantly lesser with dexmedetomidine at 4-10 min (p-value<0.05) compared to lidocaine with propopfol which is similar to our study. Anandani DN et al [15] observed that dexmedetomidine was better than lignocaine in attenuation of SBP and MAP after intubation as has been observed in our study. Samuel, H et al [16], Gurulingappa et al [6] and Thippeswamy RR et al [17] compared fentanyl vs lignocaine in reduction of pressor response and found fentanyl was better than lignocaine which is similar to our study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Seangrung et al [14] found that difference in mean values of SBP, DBP and MAP were significantly lesser with dexmedetomidine at 4-10 min (p-value<0.05) compared to lidocaine with propopfol which is similar to our study. Anandani DN et al [15] observed that dexmedetomidine was better than lignocaine in attenuation of SBP and MAP after intubation as has been observed in our study. Samuel, H et al [16], Gurulingappa et al [6] and Thippeswamy RR et al [17] compared fentanyl vs lignocaine in reduction of pressor response and found fentanyl was better than lignocaine which is similar to our study.…”
Section: Discussionsupporting
confidence: 87%
“…than the other two groups in decreasing RPP at 1 st (p-value =0.040), 3 rd (p-value=0.001), 5 th (p-value =0.001), 10 th (p-value <0.001) and 15 th (p-value =0.002) minute which was highly statistically significant. Anandani DN and colleagues compared lignocaine and dexmedetomidine in reduction of sympathoadrenal response to intubation and concluded that dexmedetomidine had more significant reduction in RPP than lignocaine and hence has superior cardio-protection in patients against hemodynamic response than lignocaine [15] which was also seen in our study. Jain V et al [12] observed that the highest elevation in RPP occurred at 1 min post intubation in the fentanyl group, with a figure of 9758.43, which was statistically higher than that of the dexmedetomidine group with mean RPP of 8185.96 at 1 min after laryngoscopy which was in concordance with our study.…”
Section: Journal Of Applied Pharmaceutical Research (Joapr)| January ...supporting
confidence: 84%